Therapeutic Strategies in the Treatment and Prevention of Preterm Labor: A Systematic Review - Alim, Fathi Nabila; Hariyati, Suheni Ninik (Asian Journal of Health Research, 2025)
Introduction: Prematurity remains the leading cause of prenatal and newborn mortality and morbidity worldwide. Numerous trials with varying degrees of efficacy have been carried out to identify therapies to prevent premature birth. Therefore, the purpose of this study is to analyze the efficacy of medications with different dosages that have been previously studied in terms of their ability to delay premature labor.    Material and Methods: The authors searched for randomized-controlled trials (RCTs) that addressed the use of therapy to prevent or treat preterm birth in pregnant patients who were either diagnosed with or at risk for preterm birth. The PRISMA approach was used to conduct the search using electronic databases, including Embase, ProQuest, PubMed, and Cochrane.    Results: We obtained 34 RCTs that met the inclusion criteria. We discovered that 400 mg of progesterone administered intravaginally consistently had a substantial effect in postponing preterm birth. Other kinds of aspirin, such as 60 mg and 81 mg, are effective in postponing premature birth. In addition, taking supplements of docosahexaenoic acid (omega-3 fatty acid) throughout pregnancy considerably delays premature birth. Preterm labor is also markedly delayed in pregnant women with HIV when selenium supplements are taken.    Conclusion: Intravaginal progesterone, oral low dose aspirin, and docosahexaenoic acid supplementation have the potential to be therapies to prevent preterm labor.